Threat biases associate with anxiety and depression in physically-abused young people with a history of child labour. (December 2022) - Sharma, Narayan Prasad; Dhakal, Sandesh; Oliver, Abigail; Gupta, Shulka; Kumari, Veena; Pandey, Rakesh; Niraula, Shanta; Lau, Jennifer Y.F.
Abstract: Background and objectives: Young people who have experienced early-life maltreatment preferentially attend to threat and draw more threatening interpretations. In turn, these threat biases may explain elevated risk for lifelong anxiety and/or depression. We investigated whether adolescent labourers with a history of physical abuse showed threat biases relative to non-abused labourers, and whether these threat biases associated with anxiety and depression. Methods: 100 young people (aged 13–18 years, 64% female) from Nepal rescued from illegal child work were assessed for childhood maltreatment and anxiety and/or depression disorders. Participants completed an emotional visual search task (to measure attention engagement of positive versus negative faces) and an ambiguous scenarios questionnaire (to measure the endorsement of negative versus benign interpretations). Results: Seventy young people reported a history of physical (and emotional) abuse. They were more likely to meet symptom thresholds for depression, and marginally, for anxiety disorders than non-physically abused participants. Abused and non-abused participants did not differ on attention engagement/disengagement of threat or on interpretational style. Abused participants with anxiety were slower to disengage from negative faces to engage with a positive face than non-anxious abused participants. Abused participants with depression endorsed more negative interpretations of ambiguous situations than those without depression. Limitations: The cross-sectional design limits our ability to infer whether threat biases reflect risk markers of psychopathology. Conclusions: If threat biases are shown to confer risk for anxiety and depression in future studies, they could be targeted in mental health prevention programs for these vulnerable young people. Highlights: Abuse status associated with meeting the symptom threshold for major depression. Abused and non-abused child labourers did not vary in biased threat processing. Abused youth with anxiety were slower to disengage attention away from threat. Abused youth with depression endorsed more negative interpretations of ambiguity.